Food crops associated with Hevea in Cote dIvoire : Resulting effect on production - Kouaio A M C; Goue B D; Keil J Z (Papers presented at IRRDB seminar 5-8 November 1996 Sri Lanka p23)
The study of the effects of different foodcrop systems, planted at 1, 2 and 3 m from Hevea rows, on the production from a lower planting density (421 trees/ha) trial and according to a double row planting scheme showed than on the one hand, the distance between foodcrops and Hevea row has no perceptible effect on production during the first two campaigns and, on the other hand, the food crop systems lead to a yield/ha some 25;higher than that of the standard plot with leguminous cover plants in the inter-rows. This higher yield appeared to be mostly related to the number of tapped trees, and thus the known precocity of Hevea trees associated with food crops, rather than the intrinsic tree production. This result was confirmed in another intercropping trial at the standard planting density (510 trees/ha) during the first four production campaigns. The difference between the results of the two trials in this second experiment gradually decrease to zero at year five of production. These results are indicative of the impact of conception between the leguminous cover plants and the Hevea trees during the immature period. The reduced competition in the case of food crops leads to a production gain from the trees at opening.
Keywords: Cote dIvoire; Food crops; Hevea; Intercropping; Yield